Understanding suicide attack: weapon of the weak or crime against humanity - Md , Yousuf Ali (Universitatea "Babes-Bolyai" * Catedra de Filosofie Sistematica, 2011)
Suicide attack has become a dangerous trend in the contemporary history of some Asian societies. While it has been used by some people as a means of protest, it has been largely rejected by humanity for its severe debilitating effects. Instances of suicide attack can be found in the contexts of the Israel-Palestine conflict, September 11 attacks, Bali bombing, Sunni-Shiite disagreement, struggle of the Tamil Tigers in Sri Lanka, as well as the occupation of Iraq and Afghanistan by foreign powers. The recent contours of suicide attacks are basically largely related to various groups or organizations. The paper therefore examines the meaning, brief history, and the causes of suicide attack, and analyzes these within the purview of contemporary Islamic thought which is based on the textual arguments of the Qur'an and Sunnah. The paper concludes that though a tiny fraction of the whole Muslim spectrum tries to justify the suicide attack as a “weapon of the weak”, the majority of the Muslim scholars has viewed it as a crime against humanity and therefore vehemently rejects this practice in any form.